MODERN VIEWS ON THE DIAGNOSIS OF COAGULOPATHIES: FACTOR II (PROTHROMBIN) DEFICIENCY - Oydinova Bakhtigul,; Umarova Tamila Abdufattoevna,; Hamzayev Javlon Maxmud o’g’li, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Coagulopathy is a group of disorders characterized by impaired normal blood clotting, which can lead to either excessive bleeding or thrombosis. In the human body, the process of blood clotting (hemostasis) ensures the cessation of bleeding after vascular injury. However, when hemostasis is impaired, various problems arise, such as excessive bleeding or, conversely, an increased tendency to form blood clots.